Hydrogen migration in inner-shell ionized halogenated cyclic hydrocarbons - Abdul Rahman Abid; Surjendu Bhattacharyya; Anbu Selvam Venkatachalam; Shashank Pathak; Keyu Chen; Huynh Van Sa Lam; Kurtis Borne; Debadarshini Mishra; René C. Bilodeau; Ileana Dumitriu; Nora Berrah; Minna Patanen; et al. (Scientific Reports, 2023)
Abstract We have studied the fragmentation of the brominated cyclic hydrocarbons bromocyclo-propane, bromocyclo-butane, and bromocyclo-pentane upon Br(3d) and C(1s) inner-shell ionization using coincidence ion momentum imaging. We observe a substantial yield of CH3 + fragments, whose formation requires intramolecular hydrogen (or proton) migration, that increases with molecular size, which contrasts with prior observations of hydrogen migration in linear hydrocarbon molecules. Furthermore, by inspecting the fragment ion momentum correlations of three-body fragmentation channels, we conclude that CH x + fragments (with x = 0, …, 3) with an increasing number of hydrogens are more likely to be produced via sequential fragmentation pathways. Overall trends in the molecular-size-dependence of the experimentally observed kinetic energy releases and fragment kinetic energies are explained with the help of classical Coulomb explosion simulations.